Vagotomy, pyloroplasty and direct ligation of the bleeding duodenal ulcer - Castiglioni, Juan C; Camaño, Mario C; Pradines, JorgeC C (Cirugía del Uruguay, 1968)
The criterion of gastrointestinal bleeding is defined as a massive one whose main cause is chronic duodenal ulcer and the advisability of early surgical intervention is indicated. The different surgical procedures used in bleeding duodenal ulcers are analyzed: vascular ligations, subtotal gastrectomy and direct ligation with vagotomy and pyloroplasty. The main clinical facts referring to 15 cases treated by direct ligation, vagotomy and pyloroplasty are presented. Postoperative results are highlighted immediate results obtained (6.6% mortality, low morbidity and no recurrence of bleeding). The need for more experience with this promising surgical procedure is noted.